Microstructure and hardness of high temperature gas nitrided aisi 420 martensitic stainless steel - Ibrahim, N.N.M. (EDP Sciences, 2014)
This study examined the microstructure and hardness of as-received and nitrided AISI 420 martensitic stainless steels. High temperature gas nitriding was employed to treat the steels at 1200Â°C for one hour and four hours using nitrogen gas, followed by furnace cooled. Chromium nitride and iron nitride were formed and concentrated at the outmost surface area of the steels since this region contained the highest concentration of nitrogen. The grain size enlarged at the interior region of the nitrided steels due to nitriding at temperature above the recrystallization temperature of the steel and followed by slow cooling. The nitrided steels produced higher surface hardness compared to as-received steel due to the presence of nitrogen and the precipitation of nitrides. Harder steel was produced when nitriding at four hours compared to one hour since more nitrogen permeated into the steel. Â© 2014 Owned by the authors, published by EDP Sciences.